Landasan Preseden, Biblikal, dan Fenomenologis terhadap Doktrin Early Evidence Baptisan Roh Kudus - Twin Yoshua R. Destyanto; Dony Lubianto; Twin Hosea Widodo Kristyanto; Kornelius Rulli Jonathans (Sekolah Tinggi Teologi Internasional Harvest Tangerang, 2022)
Since the beginning of the Pentecostal movement, the doctrine of tongues has been considered the most basic belief of the Pentecostals, as it is considered an early manifestation of the Spirit's Baptism (SB). Nevertheless, this doctrine began to fade away with the emergence of the Charismatic movement, which believed that other gifts could be the first signs of God's presence. As a result of this research, we intend to (1) demonstrate how speaking in tongue was the first evidence for SB in the Bible, (2) dig into the understanding of certain Pentecostal and non-Pentecostal theologians as to its significance, and (3) look into the experiences of ex-non-Pentecostal/Charismatic believers in experiencing the SB, in order to find out how tongues played a role in that experience. By utilizing qualitative methods with a structured literature review and phenomenology approaches to two informants, we were able to achieve these objectives. Tongues consistently function as early evidence of SB, according to the results of this study. As a result, tongues convince people who experience them or serve as an assurance for people who do not experience them to find out what SB is.